PENGARUH PEMBELAJARAN PPKn TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SMPN 4 KAMPAR KIRI TENGAH - Gilang, Wirawan; Supentri, Supentri; Hardian, Mirza (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is motivated by a phenomenon that appears based on observations made by researchers at SMPN 4 Kampar Kiri Tengah. Whereas there is a lack of student discipline character, such as; arriving late to school, not wearing a neat and complete school uniform, and long hair for male students. The formulation of the problem in this study is whether there is an influence of Civics learning on the formation of the disciplinary character of students at Middle Left Middle School 4 Kampar. The benefits of this research are theoretical benefits, namely this research is expected to contribute to the field of education, especially those related to the writing of student discipline characters. The practical benefit is to find out and get answers whether there is an effect of Civics learning on the formation of the disciplinary character of students at Middle Left Middle School 4 Kampar. The population of this study were all students of SMPN 4 Kampar Kiri Tengah, totaling 73 students. The sample in this study were 73 people with a sampling technique, namely saturated sampling. This study uses a quantitative descriptive research method. This method can be used to examine certain populations or samples, collect data using research instruments, analyze quantitative or statistical data with the aim of testing established hypotheses (Sugiyono, 2017: 15). This research method uses simple regression analysis, because the aim is to determine the effect of Civics learning on the formation of the disciplinary character of students at SMPN 4 Kampar Kiri Tengah. Data collection methods are questionnaires, observation, and documentation. Data processing with statistical analysis with a simple linear regression formula. Based on the results of research on the effect of Civics learning on the formation of the disciplined character of students at SMPN 4 Kampar Kiri Tengah. The results of the t test obtained tcount of 5,147 ttable of 1.99 which shows that tcount > ttable, so that Ho is rejected and Ha is accepted and the effect of Civics Learning on Student Discipline Character is low, From the results of the regression test it is obtained that R is obtained (R Square) of 0.272 which implies that the effect of the independent variable (CIP Learning) on ​​the dependent variable (student discipline character) is 27.2% in the